HUBUNGAN TINGKAT PENGETAHUAN DENGAN TINGKAT KESADARAN TERHADAP PENINGKATAN KESIAPSIAGAAN BENCANA KEBAKARAN DI JAKARTA - Asha Maharani; Hardin La Ramba; Shinta Prawitasari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Densely populated residential areas are highly vulnerable to fire disasters due to both technical factors, such as inadequate electrical installations, and behavioral factors, including unsafe use of fire. In addressing these risks, the capacity of the community—both at the individual and collective levels—plays a critical role in determining preparedness through knowledge and awareness of fire hazards and their potential impacts. This study aimed to examine the contribution of community knowledge and awareness to fire disaster preparedness among residents of Kalibaru Subdistrict, North Jakarta. A quantitative cross-sectional design was employed in this research. Using purposive sampling, 306 respondents were selected from an estimated population of 1,300 residents. Data were collected using structured questionnaires consisting of a fire knowledge questionnaire, a fire awareness questionnaire, and a fire disaster preparedness questionnaire, all of which had been tested for validity and reliability. The relationships among the study variables were analyzed using Spearman's rank correlation test. The results demonstrated significant positive correlations between the level of knowledge (r= 0,220, p < 0,001) and the level of awareness (r= 0,662, p < 0,001) with community preparedness for fire disasters. These findings indicate that improving community preparedness requires not only increasing knowledge through information dissemination but also strengthening public awareness to promote more adaptive behaviors toward fire risks. Therefore, community-based interventions that emphasize enhancing both knowledge and awareness are recommended as effective strategies for reducing the risk of fire disasters.